Systems and human science, for safety, security, and dependability : seleced papers of the 1st International Symposium SSR2003, Osaka, Japan, November 2003 - International Symposium on Systems and Human Science 2003 : Osaka University); Arai, Tatsuo; Yamamoto, Shigeru, 1964-; Makino, Kazuhisa; ScienceDirect eBooks (Amsterdam : Elsevier, 2005)
Our society keeps growing with a large number of complicated machines and systems, while we are spending our diverse lives. The number of aged people has been increasing in the society. It is more likely than ever that we are involved in dangers, accidents, crimes, and disasters. Securing and supporting our daily life, building reliable infrastructures against large scale disasters, and preventing unexpected human errors are crucial issues in our highly developed complex society. The systems theory can provide "modelling, decision analysis and management for safety and security" as well as "fault detection and reliable control for the design of fail-safe, fool-proof machines and systems". If the human nature is analyzed and treated properly in the process of designing machines and systems, we could create safer, more reliable, and more intelligent machines and systems that can support our society and give us no anxiety and no uneasiness. "Hybrid systems modelling human behaviours" and "services for human" could give proper examples in this respect. "Robotics for safety and security", "safety recovery systems", "visual surveillance and monitoring", and "transportation systems for safety and security", those will provide powerful tools for safe, secure, and reliable systems to achieve peaceful society. Key features: - Towards a new science and its practical applications - Analysis of humans contributing to system designs - Evaluations of systems in the aspects of sense of security and feeling of easiness. Towards a new science and its practical applications Analysis of humans contributing to system designs Evaluations of systems in the aspects of sense of security and feeling of easiness.
Multiple participant decision making in societal and technological systems / K.W. Hipel and L. Fang -- Mathematical modeling for coping with uncertainty and risk / Marek Makowski -- Managing complex and dynamic systems for the future / E.D. Jones -- Characteristics of visual attention and the safety / T. Miura, K. Shinohara, T. Kimura and K. Ishimatsu -- An agent-based rules discovery from complex database / Mina Ryoke and Yoshiteru Nakamori -- Additional learning in computational intelligence and its applications to risk management problems / H. Nakayama, K. Kuramoto, M. Arakawa and K. Furukawa -- Integrated assessment of global warming stabilization scenarios by the Asia-Pacific integrated model / Toshihiko Masui, Kiyoshi Takahashi, Mikiko Kainuma and Yuzuru Matsuoka -- Trust and acceptance of risks / Satoshi Fujii, Toshiko Kikkawa and Kazuhisa Takemura -- A value judgment for evaluating the sense of security provided by nursing care robots based on cumulative prospect theory / Hiroyuki Tamura, Yoshitomo Miura and Masahiro Inuiguchi -- A case study of resolving social dilemma among multiple municipal governments in locating a large-scale refuse incineration plant / Shinichi Fujita and Hiroyuki Tamura -- Lifecycle cost evaluation of maintenance policy : the case of the water transmission system in Kobe / K. Tanimoto, M. Matsushita and H. Tatano -- Securing fair water allocation in the Aral Sea basin / L. Fang, L.Z. Wang and K.W. Hipel -- On fault detection based on recursive subspace identification / Hiroshi Oku -- Structure of reliable controllers / N. Sebe and A. Mochimaru -- Simultaneous stabilization and its application to reliable system synthesis within a behavioral framework / Osamu Kaneko and Takao Fujii -- Fault-tolerant control using time-sharing multirate controllers / Hiroaki Kawahara, Yoshimichi Ito and Noboru Babaguchi -- Fault diagnosis for robust servo systems / K. Suzuki, A. Murakami, K. Matsumoto and T. Fujii -- A small reaction manipulator for maneuvering a GPR sensing head / H. Yabushita, Y. Hirata and K. Kosuge -- Mine detection algorithm using pattern classification method by sensor fusion : experimental results by means of GPR / Masaki Fujimoto and Kenzo Nonami -- Land mine detection algorithm using ultra-wide band GPR / T. Fukuda, K. Yokoe, T. Fukui and Y. Hasegawa -- Development of highly sensitive biosensor for explosive substances / T. Onodera, D. Ravi Shankaran, R. Harada, N. Miura, T. Sakai, K. Matsumoto, J. Liang, K. Toko and T. Imato -- Complex-valued self-organizing map : a framework of adaptive processing for multiple-frequency millimeter-wave interferometric imaging systems / Akira Hirose and Takahiro Hara -- FDTD simulation on array antenna SAR-GPR for land mine detection / T. Kobayashi, X. Feng and M. Sato -- Modeling of driver's collision avoidance behavior based on expression as hybrid dynamical system / J.H. Kim, S. Okuma, S. Hayakawa, N. Tsuchida, T. Suzuki, K. Hayashi, M. Shimizu and S. Kido -- A case study in human error modeling based on a hybrid dynamical systems approach / K. Uchida and S. Yamamoto -- Development of a UMRS (utility mobile robot for search) and a searching system for casualties using a cellphone / Toshi Takamori, Masayuki Takashima, Akihiko Ikeuchi, Shiro Takashima, Shigeru Kobayashi and Takashi Ohira -- Proposal of a wheelchair user support system using humanoid robots to create an SSR society / Kotaro Sakata, Kenji Inoue, Tomohito Takubo, Tatsuo Arai and Yasushi Mae -- A Study on localization of a mobile robot based on ID tags / Weiguo Lin, Songmin Jia and Kunitatsu Takase -- Nuclear safety ontology : basis for sharing relevant knowledge among society / K. Furuta, T. Ogure and H. Ujita -- Excavation of non-stockpile munitions in China / Hiroshi Niho -- A human-safe control for collision avoidance by a redundant robot using visual information / Jian Huang and Isao Todo -- Management system for cameras' video data in emergency / Y. Wang, Y. Hijikata and S. Nishida -- Visual object tracking based on a multi-viewpoint 3D gradient method / Takayuki Moritani, Shinsaku Hiura and Kosuke Sato -- Invariant image information and face detection in unrestricted posture / Jun'ichi Yamaguchi and Hiroshi Seike -- Head detection and tracking for monitoring human behaviors / Y. Mae, N. Sasao, Y. Sakaguchi, K. Inoue and T. Arai -- Adaptive background estimation and shadow removal in indoor scenes / Junya Morita, Yoshio Iwai and Masahiko Yachida -- Tracking people and action recognition from omnidirectional images / Akari Matsumura, Yoshio Iwai and Masahiko Yachida -- An evacuation problem in tree dynamic networks with multiple exits / Satoko Mamada, Kazuhisa Makino and Satoru Fujishige -- A proposal of both a concept and a prototype of a driver secure system / S. Washino.
"Cosponsored by Graduate School of Engineering Science, Osaka University, Society for Instrumentation and Control Engineers (SICE), Robotics Society of Japan (RSJ)."
"The First International Symposium on Systems and Human Science was successfully held in November 19 and 20, 2003, at Osaka University"--Preface.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Computational intelligence -- Congresses; Human-machine systems -- Congresses; Artificial intelligence -- Congresses; Robots -- Control systems -- Congresses; COMPUTERS -- Enterprise Applications -- Business Intelligence Tools; COMPUTERS -- Intelligence (AI) & Semantics; Artificial intelligence; Computational intelligence; Human-machine systems; Robots -- Control systems; Electronic books